Supporting Shared Decision Making When Clinical Evidence Is Low. (February 2013) - Braddock, Clarence H.
Shared decision making (SDM) is the process of providing the patient with critical information that can support his or her informed participation in decision making. Shared decision making has become accepted as an important component of quality health care. Influenced by its foundations in law and ethics and by empirical work on its value as a tool to reduce variability in care, a perception has developed that SDM is relevant primarily to clinical situations with high-quality clinical evidence. This raises the question of the role of SDM in situations when clinical evidence is lacking or of low quality. This article posits that SDM is equally relevant and important to low-evidence situations in four ways—SDM fosters shared acceptance of uncertainty, closes the gap in knowledge between patient and physician, promotes patient empowerment, and enhances trust through transparent communication.